THE EFFECT OF SCHOOL OPERATIONAL ASSISTANCE AND TRANSFORMATIONAL LEADERSHIP ON THE QUALITY OF LEARNING AND ITS IMPLICATIONS ON THE QUALITY OF EDUCATION IN PUBLIC ELEMENTARY SCHOOLS IN CIMANGGU DISTRICT PANDEGLANG REGENCY - Taryudin S, Acep; Rustandi, Tata; Permana, Angrian (International Journal of Economy, Education and Entrepreneurship (IJE3), 2025)
This research is motivated by the still weak management of BOS funds, transformational leadership, learning quality, and education quality in Public Elementary Schools in Cimanggu District, Pandeglang Regency. The purpose of this study is to analyze the influence of BOS fund management and transformational leadership on learning quality and its implications for education quality. The method used is quantitative with a population of 324 teachers and a sample of 125 respondents. The research instrument was a questionnaire with a Likert scale, while data analysis used regression with the help of Smart PLS. The results of the study indicate that BOS fund management and transformational leadership have a positive and significant effect on learning quality and education quality. In addition, learning quality is also proven to have a positive and significant effect on education quality. The conclusion of this study confirms that the better the management of BOS funds and transformational leadership, the higher the quality of learning which has an impact on improving the quality of education in Public Elementary Schools in Cimanggu District.